EFEKTIVITAS THINK PAIR SHARE TERHADAP HASIL BELAJAR IPA DITINJAU DARI SIKAP ILMIAH - Ika Prastiwi (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2017)
This study aims to determine differences in the results of science learning grade VII students between the learning using TPS and direct learning in terms of students' scientific attitudes. The population is all students of class VII of SMP Negeri 5 Banguntapan Bantul with the sample is class VII C and VII D taken by random sampling. Data collection techniques using test techniques and questionnaire techniques. Data analysis technique used one path ladder analysis. The results showed that there is a very significant difference of science learning outcomes of students of class VII SMP Negeri 5 Banguntapan Bantul 2016/2017 academic year between using the model of TPS learning and direct learning model viewed from the scientific attitude of students so that the model of learning Think Pair Share more effective in improving The results of science learning compared with Direct Instruction learning model in terms of students' scientific attitude.